Chronic unpredictable stress disturbs the blood-testis barrier affecting sperm parameters in mice - Kolbaşı, Bircan; Bülbül, Muhammet Volkan; Karabulut, Seda; Erdem Altun, Ceren; Çakıcı, Çağrı; Ülfer, Gözde; Müdok, Tangül; Keskin, İlknur (Elsevier Ltd, 2021)
Research question: Does chronic stress affect the key proteins and sperm parameters of the blood & ndash;testis barrier (BTB)? Design: C57Bl/6 mice were divided into two groups: a non-treated control group and a chronic unpredictable stress (CUS) applied group. The stress status of the animals was confirmed with behavioural tests. Histopathologic evaluation was conducted by haematoxylin and eosin staining and electron microscope. Malondialdehyde, corticosterone and testosterone levels were evaluated in peripheral blood. Expression levels of BTB proteins, namely zonula occludens-1 (ZO-1), claudin-11 (CLDN11) and clathrin in Sertoli cells, were assessed by Western blotting and immunofluorescence techniques. Sperm samples were collected from cauda epididymis, and sperm parameters analysed. Results: The stress model was confirmed by behavioural tests. Histopathological evaluation of the testes demonstrated a mild degeneration in seminiferous tubules. Malondialdehyde (P = 0.008) and corticosterone levels increased (P = 0.004) and testosterone levels decreased (P = 0.005) in the CUS group. Electron microscopic evaluation confirmed the damage in BTB integrity in the CUS group. Western blot analysis showed that ZO-1 and CLDN11 levels were significantly decreased, although clathrin levels were unchanged. Although sperm concentration and total motility rate were not significantly different between the groups, progressive motility (P = 0.03), normal sperm morphology (P = 0.04), chromatin integrity (toluidine blue) (P = 0.002) and the acrosomal reaction rate (P = 0.002) were significantly decreased, and acrosomal abnormality rate was dramatically increased (P = 0.04) in the CUS group. Conclusions: In mice, CUS disrupted BTB integrity and impaired sperm parameters. A decrease in ZO-1 and CLDN11 expression levels may be proposed as the causative factor.
Keywords: Blood-Testis Barrier; Chronic Unpredictable Stress; Sperm; Spermatogenesis; Testis